Sex and sexuality : Winnicottian perspectives - Caldwell, Lesley (Winnicott studies monograph series., 2005)
This collection provides a fresh and innovative look at the work of Winnicott and into sexuality, in particular infantile sexuality. The unusual link of Winnicott to Freud and to a psychoanalysis located in the drives encourages a different perspective into British psychoanalysis. Other diverse themes include a historical examination of Winnicott through the British Society; an exploration of the similarities between Laplanche and Winnicott; the use of Winnicott's work in the treatment of sexual dysfunction; and the interrelation between sexuality and play. This is the sixth volume in the Winn.